Pengembangan Media Pop-Up Book pada Materi Siklus Air di Kelas V SD Negeri 04 Puding Besar - Hikmah, Nur; Kuswidyanarko, Arief; H. M. Lubis, Patricia (UNIB Press, 2022)
This study aims to develop learning media in the form of a class V water cycle pop-up book that is effective, practical and effective for student learning outcomes. This study applies research and development using the ADDIE model, which consists of five stages, namely analysis, design, development, implementation, and evaluation. The research was conducted at SD Negeri 04 Puding Besar with the number of fifth grade students as many as 22 people. Data collection was carried out using media experts, linguists, material experts, student response questionnaires, and student test results data validation questionnaires. The validation of the three validators resulted in an average score of 92% in the very valid category. The results of the practicality of the student's answer questionnaire are in the very practical category with an average value of 97.18%, and the effectiveness results are obtained from the results of the test questions distributed to 22 students, 20 completed and two completed. I have not reached KKM 70 in Science. The average score of students' completeness is 82.04%, including the very effective category. From the results of these data, it can be concluded that the development of pop up book media for water circulation class V SD Negeri 04 Puding Besar is a valid, practical and effective learning media for student learning outcomes.